Covalent organic frameworks as metal-free heterogeneous photocatalysts for organic transformations - Zhi, Yongfeng; Li, Ziping; Feng, Xiao; Xia, Hong; Zhang, Yumin; Shi, Zhan; Mu, Ying; Liu, Xiaoming (Journal of materials chemistry. A, Materials for energy and sustainability, 2017)
Two-dimensional covalent organic frameworks (2D-COFs) are excellent candidates for photocatalytic organic transformations due to their periodic columnar π-arrays and ordered nanochannels. Here, we present a novel 2D-COF that features permanent porosity with high surface area and large pore volume, and exhibits a high crystallinity and an excellent stability. Indeed, the new 2D-COF was found to be a highly efficient, metal-free, recyclable heterogeneous photocatalyst for oxidative C–H functionalizations under visible-light irradiation using O 2 as a green oxygen source.